PENGARUH PROBLEM BASED LEARNING BERBANTUAN VIDEO PADA PEMBELAJARAN ENERGI BERGERAK KELAS IV - Nulhuda, Ihwan; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2025)
This study focuses on the effect of implementing a problem-based learning model assisted by video learning media on learning outcomes. The research method uses a quantitative approach, while the type of research in this study is experimental research in the form of QuasiExperimental Design. The population of this study was all grade IV consisting of 2 classes. The sample was 25 students in grade IV A and 24 students in grade IV B. The data collection technique used was the measurement technique, namely the average value of student learning outcomes in the form of values obtained from the results of tests conducted before (pretest) and after (posttest) were given. Based on data analysis, the average final test for the control class was 71.08, and the experimental class was 71.64. the results of the hypothesis test using the t-test obtained a t count of 22.9390 while dk (25 + 25 - 2 = 48) with an Î± level of 5% obtained = 2.06390 which means tcount>ttable, then ha is accepted. The calculation results using the effect size formula, obtained an effect size value of 0.78. This shows that the application of the problem-based learning model assisted by learning videos in science teaching on moving energy material influences the learning outcomes of students in class IV of State Elementary School 36 South Pontianak.